Supporting Transition: an analysis of the experience and performance of widening access students on their undergraduate degree programmes. (1st November 2019) - Annetts, Jason; Work, Hazel; Cameron, Andrea; Miller, Amy; Niitamo, Vilja; Stirling, Marnie
The paper examines the experience and performance of Abertay Access to Higher Education programme, AHEAD. The research is largely based on a qualitative analysis of two focus groups and nine in-depth, semi-structured interviews with former AHEAD students. A statistical analysis of the performance of all AHEAD students on their chosen undergraduate degrees between 2012-13 and 2016-17 was also conducted. The paper demonstrates that AHEAD is an effective alternative route to higher education and argues that university-based access courses may be better in preparing these students for the culture and rigours of university life.